2016
DOI: 10.1111/iju.13253
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus after kidney transplantation in Japanese patients: The Japan Academic Consortium of Kidney Transplantation study

Abstract: Post-transplant diabetes mellitus is a common complication in Japan, similar to that in other Western countries. The present results show that an appropriate immunosuppressive regimen with a combination of tacrolimus and mycophenolate mofetil can reduce the likelihood of developing post-transplant diabetes mellitus. Clinical trials are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…The NODAT rate was an inconclusive result. We previously reported that the TAC‐QD group was likely to have lower trough thresholds for NODAT than the TAC‐BID group …”
Section: Discussionmentioning
confidence: 96%
“…The NODAT rate was an inconclusive result. We previously reported that the TAC‐QD group was likely to have lower trough thresholds for NODAT than the TAC‐BID group …”
Section: Discussionmentioning
confidence: 96%
“…CMV infection included the presence of CMV in plasma by pp65 antigenemia, and clinical signs and symptoms attributable to CMV infection. PTDM (new‐onset diabetes after KT) was defined in accordance with the American Diabetes Association . CVD included coronary artery disease, heart failure, stroke, arrhythmia and related vascular diseases.…”
Section: Methodsmentioning
confidence: 99%
“…PTDM (new-onset diabetes after KT) was defined in accordance with the American Diabetes Association. 10 CVD included coronary artery disease, heart failure, stroke, arrhythmia and related vascular diseases. Diagnosis of CVD was recorded on medical charts by cardiologists at each center.…”
Section: End-points and Follow Upmentioning
confidence: 99%
“…PTDM is a common and serious complication of kidney transplantation. In this study, the authors evaluated the risk factors of PTDM in Japanese patients, and showed that: (i) the incidence rate of PTDM was 15.1% at 5 years, and in many cases, PTDM occurred within the first several months; (ii) the associated risk factors of PTDM included advanced age, obesity, a higher tacrolimus (TAC) trough level and the absence of mycophenolate mofetil (MMF) use; and (iii) it is possible that an optimized TAC + MMF combination regimen diminishes the risk of PTDM development, which results from both a reduced TAC trough concentration and low corticosteroid dose …”
mentioning
confidence: 99%
“…(i) the incidence rate of PTDM was 15.1% at 5 years, and in many cases, PTDM occurred within the first several months; (ii) the associated risk factors of PTDM included advanced age, obesity, a higher tacrolimus (TAC) trough level and the absence of mycophenolate mofetil (MMF) use; and (iii) it is possible that an optimized TAC + MMF combination regimen diminishes the risk of PTDM development, which results from both a reduced TAC trough concentration and low corticosteroid dose. 1 All the kidney transplant recipients who were enrolled in this study had received TAC-based immunosuppression, but its adverse effects are known to play a major role in PTDM. In general, the Asian population has a lower insulin secretion capacity than the Caucasian population.…”
mentioning
confidence: 99%